Bidirectional Volume Exchange Between Kuroshio and East China Sea Shelf Water Based on a Whole‐Region Passive‐Tracing Method. Issue 5 (13th May 2020) - Hu, Fang; Liu, Yahao; Xu, Zhenhua; Yin, Yuqi; Hou, Yijun
Abstract: The Kuroshio intrusion has a profound influence on the marine dynamic and ecological environment in the East China Sea (ECS) shelf. In most previous studies, the intrusion has been evaluated by the volume transport across the 200 m isobath. However, this approximate substitution leads to an underestimation of the Kuroshio intruding flux as it fails to separate the onshore and offshore transport of Kuroshio and shelf water. In this paper, a whole‐region passive‐tracing modeling method is proposed to quantitatively explore the bidirectional exchange of Kuroshio and shelf water, by introducing the Kuroshio water concentration as a passive tracer into the flux calculations. In terms of the climatological annual mean, the Kuroshio intrusion onto the ECS shelf is as high as 1.85 Sv (1 Sv = 10 6  m 3  s −1 ), with a shelf water outflow rate of 0.42 Sv. The real Kuroshio intruding flux is about 30% higher than the net volume transport across the 200 m isobath (1.43 Sv), which indicates that the influence of the Kuroshio intrusion on the ECS may be far greater than believed before. The volume exchange on the inner shelf of the ECS is also discussed. Analyses of the momentum balances indicate that the exchanges on both the shelf break and the inner shelf are generally dominated by the geostrophic balance, but the exchange on the shelf break is more susceptible to nonlinear effects. The results of a set of sensitivity experiments show that variation of the Kuroshio intrusion is mainly regulated by the combined effect of the Kuroshio transport, the Taiwan Strait current, and the local wind stress. In contrast, the local wind stress has a predominant effect on the outflow of shelf water. Plain Language Summary: In this paper, the intruding flux of the Kuroshio water onto the East China Sea shelf is separated from the total cross‐shelf break transport and calculated with a whole‐region passive‐tracing method, revealing a quantity that is approximately 31% higher than those of the traditional net cross‐shelf break transport methods. The results of sensitivity experiments show that the variation of the Kuroshio intrusion is mainly regulated by the combined effect of the Kuroshio transport, the Taiwan Strait current, and the local wind stress. In contrast, the local wind stress has a predominant effect on the outflow of shelf water. Key Points: A whole‐region passive‐tracing method is established for calculating the volume flux of water exchange Bidirectional volume exchange between Kuroshio and East China Sea shelf water are quantified separately Key factors affecting Kuroshio and shelf water exchanges are studied through a set of sensitivity experiments